1985
DOI: 10.1128/aac.28.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaxime and desacetylcefotaxime pharmacokinetics in infants and children with meningitis

Abstract: The pharmacokinetics and cerebrospinal fluid (CSF) penetration of cefotaxime (Ctx) and desacetylcefotaxime (dCtx) were evaluated in 13 infants and children with meningitis after dose 6 of Ctx in a multiple-dose intermittent intravenous infusion regimen (50 mg/kg every 6 h). Model-dependent and noncompartmental pharmacokinetic parameters were determined and were found to be congruous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 33 publications
4
33
2
Order By: Relevance
“…Several studies of cefotaxime disposition in adults with renal dysfunction have been published (4,6,7). Compared with adult data, several similarities with our results are (9). The results reported in our study were consistent with findings from adult studies which determined desacetylcefotaxime pharmacokinetics (4,6,7).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Several studies of cefotaxime disposition in adults with renal dysfunction have been published (4,6,7). Compared with adult data, several similarities with our results are (9). The results reported in our study were consistent with findings from adult studies which determined desacetylcefotaxime pharmacokinetics (4,6,7).…”
Section: Discussionsupporting
confidence: 83%
“…There are limited published pharmacokinetic data in pediatric patients to compare our results. Trang et al (9) reported cefotaxime pharmacokinetics after multiple dosing in a group of infants less than 3 years of age; while the t1/2 value was similar (0.81 versus 0.67 h), CLT, CLR, CLNR, and V. were all larger than those reported in our results. These differences may be due in part to differences in patient demographic characteristics, study design, and data analysis, but it is more likely that the differences stem from age differences of the children studied.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies in human have explored only cefotaxime distribution in cerebrospinal fluid (CSF) (5)(6)(7)(8). Among them, two in adults (5, 6) and one in children (7) reported CSF-to-plasma AUC ratios lower than 20%, indicating poor penetration of cefotaxime in CSF as reported now in brain (26.1 Ϯ 12.1% in the present study).…”
Section: Discussionmentioning
confidence: 62%
“…The exact location of bacteria in meningitis is still unclear. Few studies, limited to investigations in cerebrospinal fluid (CSF), were performed (5)(6)(7)(8), and they found a low central distribution of cefotaxime (5,6). In humans, the easiest way to study antibiotic penetration into CNS is to measure the concentration in CSF from lumbar puncture or external ventricular drainage.…”
mentioning
confidence: 99%
“…In addition, cefotaxime can be metabolized to desacetylcefotaxime, an active compound most similar in activity to some older cephems, such as cefuroxime (3). Favorable synergistic and additive interactions have been reported in vitro and in vivo and attributed to the presence of the desacetyl metabolite (3,17). Ceftriaxone is not significantly metabolized, but it does have >95% protein binding compared with 10 to 40% for cefotaxime or desacetylcefotaxime (13,15).…”
mentioning
confidence: 99%